2011
DOI: 10.1590/s1806-37132011000400009
|View full text |Cite
|
Sign up to set email alerts
|

Respiração bucal e anteriorização da cabeça: efeitos na biomecânica respiratória e na capacidade de exercício em crianças

Abstract: Objective: To evaluate submaximal exercise tolerance and respiratory muscle strength in relation to forward head posture (FHP) and respiratory mode in children, comparing mouth-breathing (MB) children with nasal-breathing (NB) children. Methods: This was a controlled, analytical cross-sectional study involving children in the 8-12 year age bracket with a clinical otorhinolaryngology diagnosis of MB, recruited between October of 2010 and January of 2011 from the Mouth Breather Clinic at the State University of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 25 publications
1
20
0
8
Order By: Relevance
“…In this study, most girls had lower values for inspiratory and expiratory pressures compared with boys in both groups. Similar results were observed in previous study 10 . This is because females have vital capacity (air volume that can expel from the lungs found in this study is that a good portion of respondents from mouth breathers group have monthly incomes below the minimum wage compared to the nasal breathers group and were differences between groups, corroborating the findings of other authors 12 also they found lower averages for mouth breathers group.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In this study, most girls had lower values for inspiratory and expiratory pressures compared with boys in both groups. Similar results were observed in previous study 10 . This is because females have vital capacity (air volume that can expel from the lungs found in this study is that a good portion of respondents from mouth breathers group have monthly incomes below the minimum wage compared to the nasal breathers group and were differences between groups, corroborating the findings of other authors 12 also they found lower averages for mouth breathers group.…”
Section: Discussionsupporting
confidence: 93%
“…This finding can be explained because the boys have a higher prevalence of allergic rhinitis, the main entity associated with mouth breathing, and a lower airway caliber 9 . However, according to other studies performed 8,10 there is no direct relationship from the mouth breathing, caused by allergic rhinitis, for males.…”
Section: Discussionmentioning
confidence: 84%
“…Por outro lado, nenhuma diferença foi encontrada entre RBF e RN, o que reforça a influên-cia do fator obstrutivo na postura craniocervical. Okuro et al 18 , também verificaram a presença de uma anteriorização do segmento craniocervical em 96,7% de um grupo de crianças RB e 48,4% em um grupo controle.…”
Section: Discussionunclassified
“…O estudo de Silveira et al 3 avaliou a postura por meio da fotogrametria postural e a capacidade vital forçada de crianças respiradores bucais pela espirometria, em que foram observadas alterações da angulação postural e valores reduzidos da capacidade vital forçada comparativamente ao grupo controle. A literatura aponta pouca comprovação da eficácia de tratamentos para essa síndrome em que se apresenta um grande número de alterações corporais e respiratórias 8 . Portanto, evidenciando a necessidade de intervenções tanto posturais quanto respiratórias como o que foi realizado nessa pesquisa.…”
Section: Discussionunclassified
“…Outras alterações posturais podem advir da anteriorização da cabeça, como a protrusão dos ombros; a elevação e a abdução das escápulas; a depressão da região torácica; a hiperextensão dos joelhos; os pés planos e desequilíbrios musculares 8,9 . Essas compensações podem ser explicadas pelo fato de nossos músculos serem organizados anatômica e funcionalmente relacionados por meio de cadeias musculares e agirem sinergicamente com o objetivo de manter o equilíbrio postural 3,8,10 .…”
Section: Introductionunclassified